Efek Moderasi Firm Size Dalam Pengaruh Debt Covenant, Litigation Risk Analysis And Accounting Conservatism pada Quality Profit (Studi pada Perusahaan Property & Real Estate yang Terdaftar di Bursa Efek Indonesia) - Sugeng Hariadi (Magister Ilmu Akuntansi Universitas Jambi, 2023)
The purpose of this research is to determine the moderating effect of company size in the influence of litigation risk, debt covenants, and accounting conservatism on earnings quality in manufacturing companies in the property & real estate sector which are listed on the Indonesia Stock Exchange for the 2020 period. Using the quantitative method in this study which processed using SPSS 23. For sample selection using purposive sampling technique. With the specified criteria, 36 companies can be obtained as samples. The test results show that litigation risk and debt covenants have no effect on earnings quality. Meanwhile, accounting conservatism has no effect on earnings quality. Company size also cannot or is able to moderate the effect of litigation risk and debt covenants on earnings quality, but company size can or is able to moderate the effect of accounting conservatism on earnings quality.